Porous ceramic based on high-temperature self-reaction and preparation method of ceramic-based composite material

Through the method of combining high-temperature self-reaction and fiber braided body, the problem of uneven pores of porous ceramics is solved, and the controllability of pores and the improvement of ceramic performance is achieved.

CN119430989AInactive Publication Date: 2025-02-14SICHUAN UNIV
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411740535.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing porous ceramic preparation methods are cumbersome, making it difficult to ensure the uniformity of porosity and pore distribution, and the introduced impurities are difficult to completely remove, affecting the performance of the ceramic.

Method used

The preparation method of porous silicon-based ceramics based on high temperature self-reaction is adopted. The carbon-heat reduction reaction of silicon-based ceramics occurs at high temperature to achieve adjustable and controllable pores, and the fiber braid is introduced to combine with silicon-based polymers to regulate the pore morphology. and porosity.

Benefits of technology

The uniformity of pore morphology and size of porous ceramics is achieved, the open porosity and permeability are improved, the mechanical properties are excellent, and the molding process is simple, and other impurities are not introduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430989A_ABST
    Figure CN119430989A_ABST
Patent Text Reader

Abstract

The invention provides a porous ceramic based on high-temperature self-reaction and a preparation method of a ceramic-based composite material, and belongs to the technical field of porous ceramics. The preparation method of the porous ceramic comprises the following steps: 1) preparing compact amorphous silicon-based ceramic; and 2) preparing the porous ceramic based on high-temperature self-reaction. The preparation method of the porous ceramic-based composite material comprises the preparation method of the porous ceramic. The precursor further includes a woven fiber preform. The amorphous silicon-based ceramic is subjected to a carbon thermal reduction reaction at a high temperature, and the prepared porous ceramic and the porous ceramic-based composite material are adjustable and controllable in pores, uniform in pore morphology and size, high in open porosity and excellent in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of porous ceramics, and relates to a method for preparing porous silicon-based ceramics based on high-temperature self-reaction, and specifically to a method for preparing porous ceramics and ceramic-based composite materials based on high-temperature self-reaction. Background Art

[0002] Porous ceramics have the advantages of excellent high-temperature thermal stability, corrosion resistance, wear resistance, low density, low thermal conductivity and strong adsorption capacity, and are widely used in aerospace, machinery, energy, chemical industry, environmental protection and other fields. For example, porous ceramics as filter materials have obvious advantages in filtering strong acids, strong alkalis and high-temperature liquids; as catalyst carriers, they have large specific surface area, strong adsorption capacity, good chemical stability, which is conducive to rapid reaction, and will not introduce new impurities due to the carrier. In the field of aerospace, due to its excellent high-temperature thermal stability, porous ceramics are widely used in active cooling and heat protection and passive insulation components. Common preparation methods for porous ceramics include organic template impregnation method, foaming method, pore-forming agent addition method, particle stacking method, etc. The above methods are cumbersome and usually introduce new impurities that cannot be completely removed; the raw material composition and molding process are complicated and cannot ensure uniform mixing; the type, content and sintering temperature of additives such as sintering aids are difficult to control, and ultimately have different degrees of influence on the porosity, pore distribution and pore size of porous ceramics.

[0003] For example, the invention patent with publication number CN109467438A discloses a method for photocuring molding of silicon carbide ceramics, and the specific molding steps are as follows:

[0004] 1) SiC ceramic powder (25-40 vol%), photosensitive resin (55-70 vol%), and photoinitiator (2-5 wt%) are mixed and added into a ball mill, and the mixture is ball milled for 2-10 h at a rotation speed of 300-400 r / min on a planetary ball mill, and then a dispersant (1-5 wt%) is added and the mixture is ball milled for another 1-2 h to obtain a uniformly dispersed SiC slurry; 2) The SiC slurry obtained in step 1) is printed into a SiC ceramic green body by using a photocuring molding device; 3) The SiC ceramic green body obtained in step 2) is heated from room temperature to 400 ° C. / min at a heating rate of 3-5 ° C. / min. to 200°C, then heat from 200°C to 500°C at a heating rate of 5°C / min, then heat from 500°C to 1200-1300°C at a heating rate of 10°C / min, cool to room temperature with the furnace, and take out to obtain a C / SiC blank; 4) put the C / SiC blank obtained in step 3) into a graphite crucible, and embed it with Si powder, and then place it in a vacuum sintering furnace for reaction sintering, heating rate: 10°C / min, sintering temperature: 1500-1600°C, insulation time: 1-2h; cool to room temperature with the furnace, and take out the obtained SiC ceramic part. This invention realizes the preparation of silicon carbide ceramics by photocuring molding, and the relative density can reach more than 80%, but more raw material components are introduced, and uniform mixing cannot be guaranteed.

[0005] Since single-phase porous ceramics have low strength and poor toughness, their mechanical properties are usually improved by fiber toughening, such as C f / SiC、SiC f / SiC、C f / SiCN、C f / SiBCN, etc.

[0006] The invention patent with the publication number CN116143535B discloses a method for preparing a carbon / ceramic composite material. In the process of weaving a carbon fiber preform, a ceramic mixed powder is introduced to obtain a carbon fiber preform containing a ceramic mixed powder, and then a pyrolytic carbon layer is chemically vapor deposited on the surface of the carbon fiber preform to obtain a carbon ceramic body, and then the carbon ceramic body is subjected to precursor impregnation and cracking of silicon carbide to obtain a carbon ceramic porous body, and then the carbon ceramic porous body is subjected to chemical vapor deposition pyrolytic carbon densification, and finally a reaction is carried out to melt silicon to obtain a carbon / ceramic composite material, wherein the ceramic mixed powder is composed of hafnium carbide powder, hafnium boride powder, and zirconium boride powder. This invention uses the rough layer structure pyrolytic carbon to form a close interface with the carbon fiber to improve the density, protect the carbon fiber from the high temperature erosion of silicon, and improve the high temperature resistance, mechanical properties and corrosion resistance of the composite material, but does not achieve pore control.

[0007] The invention patent with publication number CN116425559B discloses a method for preparing an oriented porous ceramic-based composite material, including the following steps: step 1, weaving silicon carbide fibers into a three-dimensional fiber skeleton by weaving; step 2, placing the three-dimensional fiber skeleton in an impregnation tank, vacuum impregnating the fiber skeleton with liquid polycarbosilane as an impregnation precursor, and after the impregnation, self-crosslinking to obtain a composite green body; solid polycarbosilane and liquid polycarbosilane are dissolved in an organic solvent as precursors to form a frozen slurry, and the composite green body and the frozen slurry are placed in a refrigeration device to solidify to form a ceramic green body, the ceramic green body is vacuum freeze-dried to remove the organic solvent, and the dried ceramic green body is self-crosslinked to obtain a cross-linked green body; step 3, high-temperature cracking under a nitrogen protective atmosphere to obtain an oriented porous ceramic-based composite material. The oriented porous ceramic-based composite material prepared by this invention has high strength, good stability, and can make the mixed gas enter the reaction chamber and mix more evenly, but it does not solve the problem of uneven pores.

[0008] It can be seen that the introduction of fibers further increases the difficulty of pore formation. The current mainstream method is to control the pores by controlling the number of impregnations during the molding process. However, this method usually forms pores or cracks between the fibers and the matrix, and cannot accurately control the pore morphology, size, uniformity and porosity.

[0009] In view of the above shortcomings, the present invention provides a method for preparing porous ceramics and ceramic-based composite materials based on high-temperature self-reaction. The high-temperature self-reaction method is used to achieve adjustable and controllable pores of silicon-based ceramics, and can also be introduced into the pore regulation of ceramic-based composite materials, thereby realizing pore regulation of ceramic-based composite materials. Summary of the invention

[0010] In view of the problems existing in the prior art, the present invention provides a method for preparing porous ceramics and ceramic-based composite materials based on high-temperature self-reaction. In the method for preparing porous ceramics and ceramic-based composite materials described in the present invention, the pores of silicon-based porous ceramics can be adjusted and controlled by carbon thermal reduction reaction of silicon-based ceramics at high temperature, and can also be introduced into the pore regulation of ceramic-based composite materials. The pore parameters in the matrix of ceramic-based composite materials are adjusted to achieve pore regulation of ceramic-based composite materials. The pore morphology and size are uniform, and the open porosity and permeability can be improved. It can be used to promote the development of porous ceramics for active cooling and heat protection and passive thermal insulation components in the field of aerospace thermal protection.

[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0012] In a first aspect, the present invention provides a method for preparing porous ceramics based on high temperature self-reaction, comprising the following steps:

[0013] 1) Preparation of dense amorphous silicon-based ceramics: dense amorphous silicon-based ceramics are prepared by precursor conversion method;

[0014] 2) Preparation of porous ceramics: In a vacuum or inert gas environment, the dense amorphous silicon-based ceramics are subjected to high-temperature self-reaction at 1400-1800° C. to obtain porous ceramics.

[0015] Preferably, the open porosity of the porous ceramic is 10-70%, more preferably 20-70%, more preferably 30-70%, and most preferably 50-70%.

[0016] Preferably, in step 1), the precursor conversion method comprises the following steps:

[0017] Curing and molding the precursor to obtain a green body; the precursor includes a silicon-based polymer;

[0018] The green body is subjected to high-temperature cracking in a vacuum or inert environment to obtain dense amorphous silicon-based ceramics.

[0019] In one embodiment, the step 1) is specifically as follows: curing the precursor to obtain a green body; the precursor includes a silicon-based polymer; the green body is subjected to high-temperature cracking in a vacuum or inert environment to obtain a dense amorphous silicon-based ceramic. Preferably, the silicon-based polymer includes modified or unmodified polycarbosilane, modified or unmodified polysilazane, modified or unmodified polysiloxane, modified or unmodified polyborosilazane. The curing molding adopts liquid molding, powder molding or photocuring molding, preferably liquid molding or powder molding. The curing molding temperature is 200-350°C, preferably 350°C, and the holding time is 1-4h, preferably 4h; the green body obtained by the curing molding is a dense and porous green body. The temperature of the high-temperature cracking is 800-1400°C, preferably 1000°C; the holding time is 2-8h, preferably 2h or 4h.

[0020] In one embodiment, the reaction temperature of the high temperature self-reaction in step 2) is preferably 1400-1800°C, more preferably 1600-1700°C, most preferably 1600°C; the insulation time of the high temperature self-reaction is 2-6h, preferably 4-6h.

[0021] The present invention enables the silicon-based ceramic to undergo a carbon thermal reduction reaction at high temperature, thereby making the pores of the silicon-based porous ceramic adjustable and controllable, and improving the open porosity.

[0022] In a second aspect, the present invention provides a method for preparing a porous ceramic-based composite material based on high-temperature self-reaction, comprising: the method for preparing the porous ceramic described in the above technical solution;

[0023] Specifically, the method for preparing the porous ceramic-based composite material comprises:

[0024] 1) Preparing dense amorphous silicon-based ceramics: curing and molding a precursor to obtain a green body; the precursor includes a silicon-based polymer and a fiber preform;

[0025] The green body is subjected to high temperature cracking in a vacuum or inert environment to obtain a dense amorphous silicon-based ceramic composite material;

[0026] 2) preparing a porous ceramic-based composite material: subjecting the dense amorphous silicon-based ceramic composite material to a high-temperature self-reaction at 1400-1800° C., preferably 1600° C., in a vacuum or inert gas environment to obtain a porous ceramic-based composite material;

[0027] Preferably, the open porosity of the porous ceramic-based composite material is 10-50%, more preferably 30-50%, and more preferably 40-50%. Preferably, the precursor comprises a silicon-based polymer and a woven fiber preform. The silicon-based polymer comprises modified or unmodified polycarbosilane, modified or unmodified polysilazane, modified or unmodified polysiloxane, modified or unmodified polyborosilazane.

[0028] The curing molding adopts the method of polymer impregnation and thermal curing; the curing molding temperature is 200-350°C, preferably 350°C, and the heat preservation time is 1-4h, preferably 4h; the green body obtained by the curing molding is a dense and porous green body;

[0029] The temperature of the high temperature cracking is 800-1400°C, preferably 1000°C; the insulation time is 2-8h, preferably 2h or 4h;

[0030] Further preferably, the precursor is a mixture of a silicon-based polymer and a fiber preform, and the steps for preparing the green body in step 1) are specifically as follows:

[0031] A chemical vapor infiltration process is used to prepare a pyrolytic carbon or BN surface coating on the fiber surface to obtain a fiber preform; under a vacuum environment, the silicon-based polymer is impregnated into the fiber preform for curing and molding to obtain a blank. More preferably, the volume ratio of the silicon-based polymer to the fiber preform is 1-2:1-2, preferably 1:1. The fiber is prepared from carbon fiber, SiC fiber or other silicon-based ceramic fiber; the preparation process is a weaving process or a stitching process. The fiber weaving method in the fiber braid can be a weaving process such as plain weave, satin weave, fiber felt, needle punching or stitching, and can also be a weaving method such as three-dimensional weaving and multi-axial weaving.

[0032] Preferably, the step 1) further comprises: repeatedly subjecting the dense amorphous silicon-based ceramic composite material obtained by high-temperature pyrolysis to silicon-based polymer impregnation and high-temperature pyrolysis. The impregnation and high-temperature pyrolysis can be repeated once or multiple times, preferably 5 times, to further obtain a dense amorphous silicon-based ceramic composite material with higher density, thereby ensuring a low linear shrinkage rate during high-temperature self-reaction. The present invention introduces a fiber braided body combined with a silicon-based polymer and utilizes the characteristics of high-temperature self-reaction of silicon-based polymers. The preparation process steps are simpler, and the prepared porous ceramic-based composite material has uniform pores, denseness, high porosity and excellent mechanical properties compared to conventional technologies, and will not cause defelting and cracking between the fiber and the matrix; at the same time, the sintering temperature is easy to control, and the porosity, pore size, mechanical properties, etc. of the porous ceramic-based composite material can be adjusted to a certain range through the self-reaction temperature and the fiber weaving method or fiber type, and the porosity control range is wide.

[0033] Preferably, in the step 2), the holding time of the high temperature self-reaction is 2-6h. The reaction temperature of the high temperature self-reaction is preferably 1400-1800°C, more preferably 1600-1700°C, and most preferably 1600°C. The temperature of the high temperature self-reaction can be changed by reducing the gas pressure conditions during sintering. The dense amorphous silicon-based ceramic composite material undergoes a carbon thermal reduction reaction (i.e., self-reaction) under high temperature conditions to obtain a porous ceramic-based composite material with high porosity and uniform pore distribution. As the self-reaction temperature increases, the average pore size and porosity increase.

[0034] In one embodiment, the chemical equation of the high temperature self-reaction is: SiO2+C→SiC+CO or Si3N4+C→SiC+N2.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] First, the method for preparing porous ceramics and porous ceramic-based composite materials using high-temperature self-reaction provided by the present invention is obtained by self-reaction of the precursor ceramic itself under high temperature conditions, the pore size and porosity are regulated by the temperature of the self-reaction, the pore morphology and size are uniform, the porosity and its control range are high, the open porosity is high, the permeability is high, the linear shrinkage is low, the mechanical properties are excellent, the stability is good, the molding process is simple, and no other impurities are introduced during the preparation.

[0037] Secondly, the porous ceramic-based composite material described in the present invention combines fiber preforms of different fiber weaving processes or stitching processes, as well as high-temperature cracking temperature and insulation time to jointly regulate the pore morphology and porosity of the porous ceramic-based composite material. The pores in the formed porous ceramics are uniformly distributed, and the open porosity and permeability are high. It will not cause defelting and cracking between the fibers and the matrix, and has excellent heat dissipation performance. It can be used to promote the development of porous ceramics for active cooling and heat protection and passive insulation components in the field of aerospace thermal protection.

[0038] Thirdly, in the method of porous ceramic-based composite materials provided by the present invention, the dense amorphous silicon-based ceramic composite materials obtained by high-temperature pyrolysis are repeatedly impregnated with silicon-based polymers and pyrolyzed at high temperature to further obtain a more dense amorphous silicon-based ceramic composite material, thereby ensuring a low linear shrinkage rate during the high-temperature self-reaction process, and then the dense amorphous silicon-based ceramic composite materials undergo self-reaction under high temperature conditions to obtain a porous ceramic-based composite material with high porosity and no significant cracks. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The morphology of porous ceramic samples obtained in Basic Examples 1-2, Examples 1-3 and Comparative Example 1;

[0040] Figure 2 XRD patterns of porous ceramic samples of Basic Example 2 and Examples 1-3;

[0041] Figure 3 The permeability of porous ceramics is tested by a self-made permeability testing device; (a) is a diagram of the self-made permeability testing device, (b)-(d) are the permeability test result diagrams of porous ceramic samples 1000℃-PIP0, 1000℃-PIP5, and 1600℃-PIP5, respectively, and (e)-(g) are the permeability test result diagrams of porous ceramic-based composite materials C / SiC-1000℃-PIP5, C / SiC-1600℃-PIP5, and C / SiC-1700℃-PIP5, respectively;

[0042] Figure 4 are scanning electron microscope images of porous ceramic materials; wherein (a)-(c) are pore images of SiC matrix based on self-reaction, and (d)-(f) are pore images of C / SiC composite materials based on self-reaction; specifically, (a) is a schematic diagram of porous ceramic sample 1700℃-PIP5 (Example 4) obtained by high-temperature self-reaction of dense ceramic sample 1000℃-PIP5 of basic Example 2 at 1700℃; (b) is an electron microscope image of porous ceramic sample 1400℃-PIP5 (Example 1); (c) is an electron microscope image of porous ceramic sample 1600℃-PIP5 (Example 3); (d), (e), and (f) are electron microscope images of C / SiC porous ceramic sample (C / SiC-1600℃-PIP5) obtained by high-temperature self-reaction of dense amorphous silicon-based ceramic composite materials at different magnifications. DETAILED DESCRIPTION

[0043] It is worth noting that, unless otherwise specified, the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.

[0044] The following is an exemplary description:

[0045] Polysilazane: PSN2 polysilazane provided by the Institute of Chemistry, Chinese Academy of Sciences;

[0046] C-Fiber:T300 Carbon Fiber.

[0047] Basic Example 1

[0048] Preparation of porous ceramic samples 1000℃-PIP0:

[0049] The polysilazane was solidified by powder molding at a curing temperature of 350° C. and a holding time of 4 hours to prepare a ceramic body.

[0050] Under an inert gas atmosphere, the green body was subjected to high-temperature pyrolysis at 1000°C for 4 hours to obtain a porous ceramic sample 1000°C-PIP0.

[0051] Basic Example 2

[0052] Preparation of dense ceramic samples 1000℃-PIP5:

[0053] (1) The polysilazane is solidified by powder molding at a curing temperature of 350° C. and a holding time of 4 h to prepare a ceramic body.

[0054] Under an inert atmosphere, the obtained embryo was subjected to high-temperature pyrolysis at 1000°C for 4 hours to obtain a porous ceramic sample 1000°C-PIP0.

[0055] (3) The obtained porous ceramic sample 1000°C-PIP0 was impregnated with polynitrogen silane and cracked. The polynitrogen silane impregnation and cracking were repeated 5 times in total to obtain a dense ceramic sample 1000°C-PIP5.

[0056] Basic Example 3

[0057] Preparation of porous ceramic-based composite material C / SiC-1000℃-PIP5:

[0058] 1) T300 carbon fiber was stitched by stitching technology with a stitching span of 2 mm to prepare a stitched carbon fiber preform.

[0059] Then, a pyrolytic carbon surface coating is prepared on the surface of the stitched carbon fiber preform by a chemical vapor infiltration (CVI) process to obtain a braided fiber preform.

[0060] Under vacuum, the silicon-based polymer polysilazane is impregnated into the braided fiber preform for curing and molding. The curing and molding temperature is 350° C. and the heat preservation time is 4 hours to obtain an embryo.

[0061] Further, the green body was subjected to high-temperature cracking at 1000°C in a vacuum environment for 4 hours to obtain an amorphous silicon-based ceramic composite material.

[0062] 2) In order to reduce the shrinkage rate of the porous ceramic composite material matrix and avoid the generation of cracks, the obtained amorphous silicon-based ceramic composite material was repeatedly impregnated with a silicon-based polymer and cracked for a total of 5 times to obtain a dense amorphous silicon-based ceramic composite material C / SiC-1000℃-PIP5.

[0063] Example 1

[0064] Preparation of porous ceramic samples 1400℃-PIP5:

[0065] Under a vacuum environment, the dense ceramic sample 1000°C-PIP5 obtained in Basic Example 2 was subjected to a high-temperature self-reaction at 1400°C for 4 hours to obtain a porous ceramic sample 1400°C-PIP5.

[0066] Example 2

[0067] Preparation of porous ceramic samples 1500℃-PIP5:

[0068] Under a vacuum environment, the dense ceramic sample 1000°C-PIP5 obtained in Basic Example 2 was subjected to a high-temperature self-reaction at 1500°C for 4 hours to obtain a porous ceramic sample 1500°C-PIP5.

[0069] Example 3

[0070] Preparation of porous ceramic samples 1600℃-PIP5:

[0071] Under a vacuum environment, the dense ceramic sample 1000°C-PIP5 obtained in Basic Example 2 was subjected to a high-temperature self-reaction at 1600°C for 4 hours to obtain a porous ceramic sample 1600°C-PIP5.

[0072] Example 4

[0073] Preparation of porous ceramic samples 1700℃-PIP5:

[0074] Under a vacuum environment, the dense porous ceramic sample 1000°C-PIP5 obtained in Basic Example 2 was subjected to a high-temperature self-reaction at 1700°C for 4 hours to obtain a porous ceramic sample 1700°C-PIP5.

[0075] Example 5

[0076] Preparation of porous C / SiC ceramic matrix composites:

[0077] 1) Preparation of dense amorphous silicon-based ceramic composite materials:

[0078] The T300 carbon fibers were stitched together by stitching technology with a stitching span of 2 mm to prepare a stitched C fiber preform.

[0079] Then, a pyrolytic carbon surface coating is prepared on the surface of the stitched C fiber preform by a chemical vapor infiltration (CVI) process to obtain a braided fiber preform.

[0080] Under vacuum, the silicon-based polymer polysilazane is impregnated into the braided fiber preform for curing and molding. The curing and molding temperature is 350° C. and the heat preservation time is 4 hours to obtain an embryo.

[0081] Further, the green body was subjected to high temperature cracking at 1000°C in a vacuum environment for 4 hours to obtain an amorphous silicon-based ceramic composite material. In order to reduce the shrinkage of the porous ceramic composite matrix and avoid the generation of cracks, the obtained amorphous silicon-based ceramic composite material was repeatedly impregnated with a silicon-based polymer and cracked for a total of 5 times to obtain a dense amorphous silicon-based ceramic composite material.

[0082] 2) Preparation of porous ceramic-based composite materials:

[0083] Under a vacuum environment, the obtained dense amorphous silicon-based ceramic composite material is subjected to high-temperature self-reaction at 1600°C for 4 hours to obtain a porous ceramic-based composite material C / SiC-1600°C-PIP5.

[0084] Example 6

[0085] Preparation of porous C / SiC ceramic matrix composites:

[0086] 1) Preparation of dense amorphous silicon-based ceramic composite materials:

[0087] The T300 carbon fiber was stitched by stitching technology with a stitching span of 2 mm to prepare a stitched carbon fiber preform.

[0088] Then, a pyrolytic carbon surface coating is prepared on the surface of the stitched carbon fiber preform by a chemical vapor infiltration (CVI) process to obtain a braided fiber preform.

[0089] Under vacuum, the silicon-based polymer polysilazane is impregnated into the braided fiber preform for curing and molding. The curing and molding temperature is 350° C. and the heat preservation time is 4 hours to obtain an embryo.

[0090] Further, the green body was subjected to high temperature cracking at 1000°C in a vacuum environment for 4 hours to obtain an amorphous silicon-based ceramic composite material. In order to reduce the shrinkage of the porous ceramic composite matrix and avoid the generation of cracks, the obtained amorphous silicon-based ceramic composite material was repeatedly impregnated with a silicon-based polymer and cracked for a total of 5 times to obtain a dense amorphous silicon-based ceramic composite material.

[0091] 2) Preparation of porous ceramic-based composite materials:

[0092] Under a vacuum environment, the obtained dense amorphous silicon-based ceramic composite material is subjected to high-temperature self-reaction at 1700°C for 4 hours to obtain a porous ceramic-based composite material C / SiC-1700°C-PIP5.

[0093] Comparative Example 1

[0094] The difference from Example 3 is that "the dense ceramic sample 1000℃-PIP5 obtained in Basic Example 2" is replaced by "the porous ceramic sample 1000℃-PIP0 obtained in Basic Example 1", and the rest is the same as Example 3, and a porous ceramic sample 1600℃-PIP0 is prepared.

[0095] Comparative Example 2

[0096] The difference from Example 5 is that "high-temperature self-reaction at 1600°C" is replaced by "high-temperature self-reaction at 1800°C", and the rest is the same as Example 5, and a porous ceramic-based composite material C / SiC-1800°C-PIP5 is prepared.

[0097] Comparative Example 3

[0098] The difference from Example 5 is that "the insulation time of the high-temperature self-reaction is 4 hours" is replaced by "the insulation time of the high-temperature self-reaction is 8 hours", and the rest is the same as Example 5, and a porous ceramic-based composite material C / SiC-1600℃-PIP5-8h is prepared.

[0099] Test example

[0100] (1) The density, linear shrinkage, open porosity and permeability of the porous ceramic samples obtained in Basic Examples 1-3, Examples 1-6 and Comparative Examples 1-3 were tested.

[0101] 1) Density detection method:

[0102] In this study, porous ceramic samples were processed into cylindrical blocks, which were then cleaned and dried by ultrasonic cleaning. The testing principle is as follows:

[0103]

[0104] Where, ρ-density of the sample, g / cm 3 ;

[0105] m-mass of the sample, g;

[0106] d-diameter of the sample, cm;

[0107] h-thickness of the sample, cm.

[0108] 2) Linear shrinkage detection method:

[0109] The linear shrinkage of the porous ceramic sample was measured using a vernier caliper and calculated according to the following formula:

[0110]

[0111] Where, δ-linear shrinkage of the specimen;

[0112] d0-diameter of the sample before high temperature treatment, mm;

[0113] d1- diameter of the sample after high temperature treatment, mm.

[0114] 3) Open porosity detection method:

[0115] This study tests the porosity of porous ceramics using the Archimedean displacement method. This method is based on the Archimedean principle, which states that the buoyancy of an object in a liquid is equal to the weight of the liquid it displaces. By measuring the volume of water displaced by the porous ceramic in the liquid, its porosity can be calculated.

[0116] The specific steps of Archimedes drainage method to measure the porosity of porous ceramics are as follows:

[0117] Prepare the sample: First, pre-treat the porous ceramic sample, including cleaning and drying, to ensure the accuracy of the measurement results. Grind away the impurities on the surface of the ceramic with a grinder, clean it, and dry it for later use.

[0118] Measure dry weight: Place the dry porous ceramic sample on an electronic balance and measure its dry weight, recorded as m1.

[0119] Immerse, boil and cool: Immerse the ceramic sample completely in a beaker of distilled water and boil it until there are no bubbles attached to the sample surface and no bubbles emerge from the water. Turn off the power and let it stand to cool.

[0120] Measure the suspended weight: Take out the ceramic sample, quickly and gently wipe off the moisture on its surface with absorbent paper, put it into the floating weight weighing instrument and weigh it, recorded as m2.

[0121] Measure wet weight: Take out the ceramic sample, quickly wipe off the moisture on its surface with absorbent paper, and then place it on the electronic balance again to measure its wet weight, recorded as m3.

[0122] Calculate porosity: According to Archimedes' principle, the volume of water displaced by a ceramic sample is the volume of the pores. By calculating the weight of the displaced water (i.e., buoyancy), the volume of the pores can be deduced. Combining the dry weight, floating weight, and wet weight of the sample, the porosity can be calculated. The formula for calculating porosity is:

[0123]

[0124] Where: V is the open porosity, m1 is the dry weight of the sample in air (g), m2 is the suspended weight of the sample in water (g), and m3 is the mass of the sample in air after fully absorbing water (g).

[0125] 4) Permeability detection method:

[0126] In this study, the permeability of porous ceramics was tested using a self-made permeability test device. Figure 3 As shown in (a), the test standard is based on the National Standard of the People's Republic of China GB / T 1969-1996 "Test Method for Permeability of Porous Ceramics". The permeability calculation formula derived from Darcy's law is as follows:

[0127]

[0128] Where: k is the permeability (m 2 ), m is the mass of water flowing through the porous medium (kg), l is the thickness of the porous medium material (m), p is the pressure difference between the inside of the pipe and the atmospheric pressure (Pa), μ is the dynamic viscosity of water, and A is the cross-sectional area of ​​the pipe outlet (m 2 ), t is the water flow time (s), ρ is the water density (kg / m 3 ).

[0129] The properties of the porous ceramic samples obtained in Basic Examples 1-2, Examples 1-6 and Comparative Examples 1-3 are shown in Table 1. Figure 1 Morphological diagram of porous ceramic samples obtained from Basic Examples 1-2, Examples 1-3 and Comparative Example 1.

[0130] Based on the self-made permeability test device, the porous ceramics prepared in basic examples 1-3, examples 1-4 and comparative example 1 and the C / SiC porous ceramic-based composite materials prepared in examples 5-6 and comparative examples 2-3 were tested for permeability. The results are shown in Tables 1 and Figure 3 As shown, Figure 3The permeability of porous ceramics was tested using a self-made permeability test device. (a) is a diagram of the self-made permeability test device, where "water flow-0.2Mpa" indicates that the water flow pressure of the permeability test is 0.2Mpa. (b)-(d) are the permeability test result diagrams of porous ceramic samples 1000℃-PIP0, 1000℃-PIP5, and 1600℃-PIP5, respectively. (e)-(g) are the permeability test result diagrams of porous ceramic matrix composites C / SiC-1000℃-PIP5, C / SiC-1600℃-PIP5, and C / SiC-1700℃-PIP5, respectively. The test results show that high-temperature self-reaction can significantly improve the permeability of porous ceramics.

[0131] By comparing Basic Example 1 with Comparative Example 1, it can be found that high-temperature self-reaction can significantly increase the open porosity and permeability of the porous ceramic sample.

[0132] By comparing Basic Example 2 with Examples 1-4, it can be found that when the high-temperature self-reaction temperature is in the range of 1400-1700°C, the open porosity increases with the increase of the high-temperature self-reaction temperature; when the high-temperature self-reaction temperature increases from 1600°C to 1700°C, the open porosity of the porous ceramic does not increase significantly.

[0133] By comparing Basic Example 3 with Examples 5-6, it can be found that high-temperature self-reaction can significantly increase the open porosity and permeability of the C / SiC porous ceramic-based composite material samples.

[0134] By comparing Examples 5-6 with Comparative Example 2, it can be found that when the high-temperature self-reaction temperature reaches 1800° C., the open porosity and permeability of the porous ceramic-based composite material are significantly reduced.

[0135] By comparing Example 5 with Comparative Example 3, it can be found that after the holding time of the high-temperature self-reaction is increased from 4 hours to 8 hours, the density of the porous ceramic-based composite material does not change significantly, and the porosity and permeability decrease significantly.

[0136] Table 1 Properties of porous ceramics and C / SiC porous ceramic matrix composite materials

[0137]

[0138] (2) The crystal structure of the porous ceramic samples prepared in Basic Example 2 and Examples 1-3 was detected. The XRD patterns were as follows: Figure 2 As shown, 1000°C represents the XRD spectrum of the porous ceramic sample of Basic Example 2, 1400°C represents the XRD spectrum of the porous ceramic sample of Example 1, 1500°C represents the XRD spectrum of the porous ceramic sample of Example 2, and 1600°C represents the XRD spectrum of the porous ceramic sample of Example 3.

[0139] Figure 2 The results show that within the range of 1000-1600℃, the structure of β-SiC increases significantly with increasing temperature. After high temperature cracking at 1000℃, no carbothermal reduction reaction occurs, and the thermal stability and conductivity are poor.

[0140] (3) Pore characteristics of SiC porous ceramics and C / SiC porous ceramic-based composites prepared by high-temperature self-reaction

[0141] The SiC porous ceramics prepared in Basic Example 2, Example 1, and Example 3 and the C / SiC porous ceramic-based composite material prepared in Example 5 were examined by electron microscopy. The results are as follows: Figure 4 As shown; (a)-(c) are pore diagrams of SiC matrix based on self-reaction, and (d)-(f) are pore diagrams of C / SiC composite materials based on self-reaction; specifically, (a) is a schematic diagram of the dense ceramic sample 1000℃-PIP5 of Basic Example 2 after high-temperature self-reaction at 1700℃ to obtain a porous ceramic sample 1700℃-PIP5 (Example 4). During the high-temperature self-reaction process, the open porosity increased from 10.8% to 62.97%, and the reaction formula was SiCN→SiC. Specifically, α-Si3N4+3C→3β-SiC+2N2↑; (b) is the electron microscope image of the porous ceramic sample 1400℃-PIP5 (Example 1); (c) is the electron microscope image of the porous ceramic sample 1600℃-PIP5 (Example 3), in which the red arrow, yellow arrow and yellow ellipse all represent the sample pores; (d), (e) and (f) are electron microscope images of C / SiC porous ceramic composite materials obtained after the dense amorphous silicon-based ceramic matrix composite material is subjected to a high temperature self-reaction at 1600℃ at different magnifications. The results show that the present invention can significantly improve the pore uniformity of the ceramic matrix composite material by introducing carbon fiber into the silicon-based ceramic matrix, and the silicon-based ceramic matrix is ​​tightly combined with the carbon fiber.

[0142] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing porous ceramics based on high temperature self-reaction, characterized in that: The following steps are involved: 1) Preparation of dense amorphous silicon-based ceramics: dense amorphous silicon-based ceramics are prepared by precursor conversion method; 2) Preparation of porous ceramics: In a vacuum or inert gas environment, the dense amorphous silicon-based ceramics are subjected to high-temperature self-reaction at 1400-1800° C. to obtain porous ceramics.

2. The method for preparing porous ceramics according to claim 1, characterized in that: The open porosity of the porous ceramic is 10-70%; in the step 1), the precursor conversion method comprises the following steps: The precursor is cured and molded to obtain a green body; the precursor includes a silicon-based polymer; the curing molding is carried out by liquid molding, powder molding or light curing molding; the curing molding temperature is 200-350° C., and the heat preservation time is 1-4 hours; The green body is subjected to high-temperature cracking in a vacuum or inert environment to obtain dense amorphous silicon-based ceramics.

3. A method for preparing a porous ceramic-based composite material based on high-temperature self-reaction, characterized in that: Prepare a porous ceramic-based composite material according to the porous ceramic preparation method of claim 2; The method for preparing the porous ceramic-based composite material comprises: 1) Preparing dense amorphous silicon-based ceramics: curing and molding a precursor to obtain a green body; the precursor includes a silicon-based polymer and a fiber preform; The green body is subjected to high temperature cracking in a vacuum or inert environment to obtain a dense amorphous silicon-based ceramic composite material; 2) Preparing a porous ceramic-based composite material: in a vacuum or inert gas environment, subjecting the dense amorphous silicon-based ceramic composite material to a high-temperature self-reaction at 1400-1800° C. to obtain a porous ceramic-based composite material.

4. The method for preparing a porous ceramic-based composite material according to claim 3, characterized in that: The silicon-based polymer includes modified or unmodified polycarbosilane, modified or unmodified polysilazane, modified or unmodified polysiloxane, and modified or unmodified polyborosilazane.

5. The method for preparing a porous ceramic-based composite material according to claim 3, characterized in that: The precursor is a mixture of a silicon-based polymer and a braided fiber preform. The steps for preparing the embryo in step 1) are specifically as follows: A pyrolytic carbon or BN surface coating is prepared on the fiber surface by adopting a chemical vapor infiltration process to obtain a fiber preform; and the silicon-based polymer is impregnated into the fiber preform under a vacuum environment for curing and molding to obtain a green body.

6. The method for preparing a porous ceramic-based composite material according to claim 5, characterized in that: The fiber is prepared from carbon fiber, SiC fiber or other silicon-based ceramic fiber; the preparation process is a weaving process or a stitching process.

7. The method for preparing a porous ceramic-based composite material according to claim 5, characterized in that: Step 1) also includes: repeatedly subjecting the dense amorphous silicon-based ceramic composite material obtained by high-temperature pyrolysis to silicon-based polymer impregnation and high-temperature pyrolysis.

8. The method for preparing a porous ceramic-based composite material according to claim 3, characterized in that: In the step 2), the heat preservation time of the high temperature self-reaction is 2-6 hours; and the open porosity of the porous ceramic-based composite material is 10-50%.

9. The method for preparing a porous ceramic-based composite material according to claim 3, characterized in that: In the step 1), the curing is performed by polymer impregnation and thermal curing; the curing temperature is 200-350° C., and the heat preservation time is 1-4 hours.

10. The method for preparing a porous ceramic-based composite material according to claim 3, characterized in that: In the step 1), the temperature of high temperature cracking is 800-1400° C., and the insulation time is 2-8 hours.

Citation Information

Patent Citations

  • Photocured molding method for SiC ceramics

    CN109467438A

  • A method for preparing carbon / ceramic composite material

    CN116143535B

  • A method for preparing oriented porous ceramic matrix composite material

    CN116425559B

  • Preparation method of silicon carbide and silicon carbide composite material member

    CN103387405A

  • Preparation method for low-density refractory and antioxidative carbon-ceramic composite material

    CN106565262A